Development and validation of a finite element model of a small female pedestrian. Issue 16 (9th December 2020) - Pak, Wansoo; Meng, Yunzhu; Schap, Jeremy; Koya, Bharath; Gayzik, F. Scott; Untaroiu, Costin D.
Abstract: Pedestrians are the most vulnerable road user and represent about 23% of the road traffic deaths in the world. A finite element (FE) model corresponding to a 5 th percentile female pedestrian (F05-PS) was developed by morphing the Global Human Body Models Consortium (GHBMC) 50 th percentile male pedestrian (M50-PS) model to the reconstructed geometry of a recruited small female subject. The material properties of the pedestrian model were assigned based on GHBMC M50-PS model. In model validation, the knee lateral stiffness and force time histories of F05-PS upper body showed similar trends, but softer responses than the corresponding data recorded in post mortem human surrogate (PMHS) tests and linearly scaled to average male anthropometry. Finally, the pedestrian model was verified in a Car-to-Pedestrian Collison (CPC) simulation. The marker trajectories recorded in simulation were close to the data recorded on small PMHS in testing and the model predicted typical knee ligament ruptures. Therefore, we believe the F05-PS model, the first FE model developed based on a female reconstructed geometry, could be used to improve vehicle front-end design for pedestrian protection and/or to investigate various pedestrian accidents.